2020
DOI: 10.1111/cei.13476
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling 1 inhibits the maturation of dendritic cells involving the nuclear factor kappa B signaling pathway in the glioma microenvironment

Abstract: Summary Recurrence and diffuse infiltration challenge traditional therapeutic strategies for malignant glioma. Immunotherapy appears to be a promising approach to obtain long‐term survival. Dendritic cells (DCs), the most specialized and potent antigen‐presenting cells (APCs), play an important part in initiating and amplifying both the innate and adaptive immune responses against cancer cells. However, cancer cells can escape from immune surveillance by inhibiting maturation of DCs. Until the present, molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…9,44 DCs are bone marrow-derived, specialized antigen-presenting cells (APCs) that function within the immune system to bridge innate and adaptive immunity. 45 As dominant APCs, DCs capture tumor antigens and present them to antigen-specific T cells via MHC glycoproteins, thereby activating naive T cells and initiating specific immune responses. 46 Upon pathogen sensing, populations of DCs in peripheral tissues become activated and migrate to the T-cell areas of draining lymph nodes (LNs), where they stimulate antigen-specific T-cell responses to initiate immunity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,44 DCs are bone marrow-derived, specialized antigen-presenting cells (APCs) that function within the immune system to bridge innate and adaptive immunity. 45 As dominant APCs, DCs capture tumor antigens and present them to antigen-specific T cells via MHC glycoproteins, thereby activating naive T cells and initiating specific immune responses. 46 Upon pathogen sensing, populations of DCs in peripheral tissues become activated and migrate to the T-cell areas of draining lymph nodes (LNs), where they stimulate antigen-specific T-cell responses to initiate immunity or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…DCs are bone marrow‐derived, specialized antigen‐presenting cells (APCs) that function within the immune system to bridge innate and adaptive immunity 45 . As dominant APCs, DCs capture tumor antigens and present them to antigen‐specific T cells via MHC glycoproteins, thereby activating naive T cells and initiating specific immune responses 46 .…”
Section: Discussionmentioning
confidence: 99%
“…DCs are bone marrow-derived, specialized antigen-presenting cells (APCs) that function within the immune system to bridge innate and adaptive immunity [32]. They are present in almost all tissues wherein they detect pathogens and process extracellular and intracellular antigens for presentation to T cells in the context of major histocompatibility complex (MHC) molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tumour-conditioned medium (TCM) collected from the supernatant of human primary glioma cells can upregulate the expression of suppressor of cytokine signalling 1 (SOCS1) in DCs and then inhibit the NF-κB signalling pathway, thereby limiting the maturation of DCs. The subsequent suppression of T-cell activity, as well as IFN-γ secretion, results in immune escape of glioma cells ( 214 ). A previous study revealed that mouse gliomas have the ability to secrete cell factors including TGF-β and IL-10 ( 215 ).…”
Section: The Role Of Ros In the Glioma Tmementioning
confidence: 99%